Photothermal microscopy applied to the characterization of nuclear fuel pellets - Zaldivar Escola, Facundo (2012)
The photothermal photodeflection technique is shown to provide information on the homogeneity of fuel pellets, pore distribution, clustering detection of pure urania and gadolinea and to provide a two-dimensional mapping of the thermal diffusivity correlated to the composition of the interdiffused Gadolinium and Uranium oxide. Histograms of the thermal diffusivity distribution become a reliable quantitative way of quantifying the degree of homogeneity and the width of the histogram can be used as a direct measure of the homogeneity. These quantitative measures of the homogeneity of the samples at microscopic levels provides a protocol that can be used as a reliable specification and quality control method for nuclear fuels, substituting with a single test a battery of expensive, time consuming and operator dependent techniques.